Maximisation of Buckling Resistance in Structural Members Made of Circular Hollow Sections - Walentyński, Ryszard; Siwek, Monika (Computer Assisted Methods in Engineering and Science; Vol 27 No 1 (2020), 2020)
This paper deals with the optimisation of the joint for thin-walled compressed elements that have circular hollow sections (CHS). A steel pipe is studied that has 3 m length, 52.3 mm diameter and 3 mm thick wall. Few examples of joint shapes are proposed. The first of them uses two extra plates that are perpendicular to the circular section. They are both in the shape of an isosceles triangle with 100 mm long and 3 mm thick sides. The second option uses four of those triangle plates. The next step is to provide perforation only in the joint area as well as along the whole element. The last option is to use a short smaller pipe inside the base pipe. Results have been compared to each other and conclusions are summarised.